Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 261626 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "TaxonKey is Garcinia L.", "TaxonKey is Cornus L.", "TaxonKey is Maytenus Molina", "TaxonKey is Sedum Adans., 1763" ] }, "HasCoordinate is true" ] } The dataset includes 261626 records from 765 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0007512-160623103540712/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences